Analisa Peracangan Prototype Arsip Surat di Dinas Lingkungan Hidup Kota Madiun - Saputro, Tobi Dwiongko; Al-ayyubi, Farras Raihan (LPPM Universitas Merdeka Madiun, 2021)
Abstract— The Madiun Environment Agency in the Field of Environmental Pollution Control has problems with archiving letters, managing incoming and outgoing letters in the Field of Environmental Damage Pollution Control still using a convental way which means that the filing of letters still uses the agenda book. It can cause damage to the agenda book and in archiving takes a long time. Mail archive information system will help make it easier for admins to manage mail archives quickly, precisely and efficiently. With the design of this prototype, it is expected that there will be no more problems in recording or managing incoming and outgoing letters at the Madiun Environment Agency. The purpose of this research is to analyze and design a prototype of The Mail Archive Information System, using unified modeling language (UML) system modeling methods. The system is designed with the feature of managing incoming mail data, managing outgoing mail data and managing incoming and outgoing mail data reports. The need to add features to print incoming and outgoing mail in order to be created for annual reports in their respective fields. This prototype information system needs to be developed and implemented at the Madiun Environment Agency as a solution to the archives of incoming and outgoing mail. Keywords—: Archive; UML; Prototype; Analysis.